Bordetella parapertussis outbreak in Southeastern Minnesota and the United States, 2014. Issue 20 (May 2017) - Karalius, Vytas P.; Rucinski, Stefanea L.; Mandrekar, Jayawant N.; Patel, Robin
Abstract : Abstract: Whooping cough is traditionally ascribed to Bordetella pertussis ; however, Bordetella parapertussis can cause a similar clinical syndrome. This study describes an outbreak of B. parapertussis in Southeastern Minnesota and the United States (US) in 2014. This was a retrospective analysis of Mayo Clinic and Mayo Medical Laboratories patients who tested positive for B. parapertussis from 2012 to 2014. The medical records of Mayo Clinic patients who tested positive in 2014 were reviewed for demographic information, presenting symptoms, disease course, and vaccination history. In Southeast Minnesota, 81% of the 31 patients who tested positive for B. parapertussis in 2014 were found to be positive from October through December. Their mean age was 5.9 years. Five reported "exposure to pertussis." Two pairs of siblings were affected. Patients reported having had symptoms for an average of 2.6 weeks before nasopharyngeal specimen collection for B. parapertussis testing. Cough was the primary symptom reported. Forty percent reported posttussive vomiting, 40% coryza, 32% apnea/sleep disturbance, and 12% sore throat. All were current with pertussis vaccination. Based on the review of national data, an outbreak occurred nationally in the Northeast and Midwest US over the same time period. In 2014, there was an outbreak of B. parapertussis in Southeastern Minnesota and likely other parts of the US. The presenting illness was similar to that of B. pertussis. All patients were vaccinated against pertussis, suggesting that pertussis vaccination is ineffective against B. parapertussis .